Seroprevalence of major avian respiratory diseases in broiler and sonali chicken in selected areas of Bangladesh (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study was conducted to investigate different respiratory diseases in broiler and sonali birds in some selected districts of Bangladesh.Materials and Methods: We were collected a total of 460 blood samples from 46 farms with 36 broiler farms and 10 sonali farms (cross-breed) from 2015 to 2017. All the collected serum samples were tested for determining specific antibodies of avian rhinotracheitis (ART) virus, infectious laryngotracheitis (ILT) virus, infectious bronchitis (IBV) virus, and Ornithobacterium rhinotracheale (ORT) infection using commercially available enzyme-linked immunosorbent assay kits.Results: The overall seropositivity was highest in ORT (45.9%), followed by IBV (37.6%), ART (2.6%), and ILT (0.4%). Out of 360 broiler samples, highest seropositivity was recorded in ORT (43.3%) and lowest in IBV (31.4%). Surprisingly, no broiler samples were found positive for ART and ILT. In case of sonali, the seropositivity was highest in IBV (60%) and lowest in ILT (2%). With respect to types of birds and age groups, the seropositive percentage of all four pathogens was found higher in sonali than broiler. Between two age groups of sonali, the seropositive percentage of ART (12%), ORT (55%), ILT (2%), and IBV (60%) was highest at 21–60 weeks of age compared to 5–20 weeks of age. However, based on location, the seropositive of ORT and IBV was highest in Jamalpur (63.3%) and Fulbariya and Trishal (50%) and lowest in Sreepur (16.7%) and Jamalpur (3.3%).Conclusion: The four pathogens are ubiquitous in nature for the sonali chickens, and the prevalence of ORT and IBV was the most prevalent viruses in the study areas. This study indicates a need for improved surveillance and characterization of ORT and ART circulating in all types of poultry in Bangladesh.J. Adv. Vet. Anim. Res., 6(4): 561-566, December 2019